Legacy of historical litter raking in temperate forest plant communities. (17th June 2018) - Vild, Ondřej; Šipoš, Jan; Szabó, Péter; Macek, Martin; Chudomelová, Markéta; Kopecký, Martin; Suchánková, Silvie; Houška, Jakub; Kotačka, Martin; Hédl, Radim
Abstract: Question: European temperate forests have been managed for millennia, and this management has left a long‐lasting legacy in soil chemistry and plant species composition and diversity. One of the most common practices was the raking of leaf litter, which was used as bedding for farm animals. We asked, what is the legacy of historical litter raking for contemporary forest plant communities? Location: Czech Republic. Methods: We explored the effect of historical litter raking on species richness and diversity of the forest herbaceous layer. We also tested whether long‐term soil acidification and nutrient depletion caused by litter raking were reflected in Ellenberg indicator values for nutrients and soil reaction and in the higher abundance of specialists of acidophilous forest types. We used written historical evidence to identify areas where litter raking was practised in the 19th century. We analysed the differences between vegetation plots located in areas affected and unaffected by the past litter raking. Our analysis included almost 2, 500 vegetation plots recorded between 1980 and 2015. Results: Litter raking was historically practised in a striking 85% of forested townships. Although litter raking had no significant effect on overall species richness, we found significant differences of diversity patterns among forest types. Historically raked plots were taxonomically more similar. We found no difference in the mean Ellenberg indicator values for soil reaction and nutrients between the affected and unaffected plots, and only a weak positive response of selected herb species of acidophilous forests. Conclusions: We provide the first empirical evidence of the historical litter‐raking legacy in forest communities on a large scale. Despite its historical frequency, we found only a weak legacy of historical litter raking in present‐day plant communities. Future studies could potentially use other, finer‐scale methods in smaller territories to complement our results. Abstract : We used written historical evidence to explore the effects of historical litter raking on the species richness and diversity of the present forest herbaceous layer. Although there are several sources of uncertainty in our data, we provide the first quantitative evidence that historical litter raking left a weak but persistent legacy in the forest understorey.